2023
DOI: 10.3390/ma16124410
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Study of Non-Explosive Simulated Blast Loading on Reinforced Concrete Slabs

Abstract: This study presents a non-explosive method for simulating blast loading on reinforced concrete (RC) slabs. The method involves using a newly developed blast simulator to apply a speedy impact load on the slab, which generates a pressure wave similar to that of an actual blast. Both experimental and numerical simulations were carried out to evaluate the effectiveness of the method. The experimental results showed that the non-explosive method can produce a pressure wave with a peak pressure and duration analogo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…It is worth noting that when the ellipsoid thickness h2 reaches 60 mm the peak pressure decreases, and the impulse begins to show a decreasing trend. This correlation can be illustrated by Equations ( 18) and (19).…”
Section: Effect Of Ellipsoid Rubber Thicknessmentioning
confidence: 95%
See 3 more Smart Citations
“…It is worth noting that when the ellipsoid thickness h2 reaches 60 mm the peak pressure decreases, and the impulse begins to show a decreasing trend. This correlation can be illustrated by Equations ( 18) and (19).…”
Section: Effect Of Ellipsoid Rubber Thicknessmentioning
confidence: 95%
“…A new impact-based facility has been developed that vertically launches multi-mass impact modules to load large-size members at precisely high velocities (VMLH). Xiong Zhixiang et al [ 19 ] used the VMLH Blast Simulator to conduct two sets of impact tests: one set of tests selected a range of flat rubber thicknesses from 20 to 100 mm and impact velocities of approximately 15 m/s; the other set used conical rubbers arranged in a 5 × 5 arrangement, with impact velocities set from 10 to 25 m/s. The results show that prismatic conical rubber is more suitable than flat rubber as an impact pad for simulating blast loads.…”
Section: Finite Element Modellingmentioning
confidence: 99%
See 2 more Smart Citations
“…Xiong et al [9] proposed a non-explosive method to simulate the explosion load of reinforced concrete slabs, and conducted experiments and numerical simulations to evaluate the effectiveness of this method. The experimental results showed that there was almost no difference between the pressure wave and the pressure peak produced by the simulated explosion load and the actual explosion.…”
mentioning
confidence: 99%